(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article is devoted to the disclosure of the features of the current stage of the state of interethnic relations as a factor in the social stability of the Republic of Uzbekistan, the issues of improving legislation in the field of relations between nations, in particular, the need to adopt a law on the state language in a new edition, taking into account the ethnic composition of the multinational population of Uzbekistan. It is argued that the adoption of the law on language in the New Edition will contribute both to the preservation and transmission to future generations of the historical and spiritual heritage associated with the Uzbek language, as well as to the improvement of the language policy in the country, as well as further strengthening of interethnic harmony. It is emphasized that the preservation of balanced interethnic relations is possible only by deepening democratic reforms in the country, creating an atmosphere of tolerance in society, and improving the culture of interethnic communication.